2013
DOI: 10.4062/biomolther.2012.093
|View full text |Cite
|
Sign up to set email alerts
|

The Spermatogenic Effect of Yacon Extract and Its Constituents and Their Inhibition Effect of Testosterone Metabolism

Abstract: We screened the pharmacological effects of a 50% ethanol extract of Yacon tubers and leaves on spermatogenesis in rats. As a result, we found that Yacon tuber extracts increased sperm number and serum testosterone level in rats. It has been reported that the crude extract of Yacon tubers and leaves contain phenolic acids, such as, chlorogenic acid, ferulic acid and caffeic acid by HPLC/MS analysis. We were interested in the contributions made by phenolic acid, particularly chlorogenic acid of Yacon tuber extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…(2019). The possible beneficial effect of FA on male reproductive hormones is due to the ability of FA to inhibit testosterone degradation enzyme in the liver (Park & Han, 2013) and/or prevent Cd from inducing overproduction of ROS. The latter is appearing to target both Sertoli and Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…(2019). The possible beneficial effect of FA on male reproductive hormones is due to the ability of FA to inhibit testosterone degradation enzyme in the liver (Park & Han, 2013) and/or prevent Cd from inducing overproduction of ROS. The latter is appearing to target both Sertoli and Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that flavonoids and amyrin inhibited spermatogenesis [31][32][33]. On the other hand, chlorogenic acid was found to stimulate spermatogenesis by inhibiting testosterone degradation [34]. However, the difference in the effects of the two extracts (root and whole plant) cannot be explained based on these compounds since these compounds were found in both the root and whole plant aqueous extracts.…”
Section: Discussionmentioning
confidence: 93%
“…A study developed by Park and Han[ 37 ] showed that leaves and tubers of Smallanthus sonchifolius (Yacon, Asteraceae ), which are rich in antioxidant compounds such as FA and CAPE, increased sperm number and serum testosterone level in rats, similarly to described for propolis.…”
Section: Discussionmentioning
confidence: 98%